Analysis, scheduling and planning in wafer fabrication systems - Citra Pramesti (2014)
The purpose of this project is to improve wafer fabrication efficiency by providing insights to wafer fabrication facility (fab) operation. Specifically, the authors are working on the analysis, planning and scheduling of the wafer fabrication system for Chartered Semiconductor Manufacturing Limited. The three individual themes are closely interlinked with emphasis on the operational planning of the fab.